To explain the steps taken to solve the equation \( n + (n - 1.5) = 8 \), we will fill in the rationale for each step based on algebraic properties.
Given: \( n + (n - 1.5) = 8 \)
Step 1: \( 2n - 1.5 = 8 \)
Rational: Combining like terms
Explanation: In this step, Ms. Jones combined the two terms \( n \) and \( n - 1.5 \) on the left-hand side of the equation. The two like terms \( n \) and \( n \) combine to \( 2n \), and the constant \(-1.5\) remains, giving the equation \( 2n - 1.5 = 8 \).
Step 2: \( 2n = 9.5 \)
Rational: Adding \( 1.5 \) to both sides
Explanation: In this step, Ms. Jones isolated the term \( 2n \) by adding \( 1.5 \) to both sides of the equation. This is done to move the constant term to the right-hand side, yielding \( 2n = 8 + 1.5 \) or \( 2n = 9.5 \).
Step 3: \( n = 4.75 \)
Rational: Dividing both sides by \( 2 \)
Explanation: In this step, Ms. Jones solved for \( n \) by dividing both sides of the equation by \( 2 \). This is an application of the division property of equality, which states that if you divide both sides of an equation by the same non-zero number, the two sides remain equal. Thus \( n = \frac{9.5}{2} = 4.75 \).
Putting it all together:
- Step 1: Rational: Combining like terms
- Step 2: Rational: Adding \( 1.5 \) to both sides
- Step 3: Rational: Dividing both sides by \( 2 \)